Histologic evaluation of chitosan as an accelerator of bone regeneration in microdrilled rat tibias - Fatemeh Ezoddini-Ardakani; Alireza Navabazam; Farhad Fatehi; Mohamad Danesh-Ardekani; Somayyeh Khadem; Gholamreza Rouhi (Wolters Kluwer Medknow Publications, 2012)
Background: Chitosan compounds have been shown to be suitable bone replacement materials. To evaluate the accelerating effects of chitosan on the bone regeneration process and assessing its histopathological adverse effects, we conducted this study on rat tibias. Materials and Methods: In a laboratory experimental study, micro-drilled bone defects were created in the upper tibia of each leg in 15 adult male rats. The defect in the right leg, filled by the chitosan powder, was compared with the untreated defect in the left leg in each rat at 1, 2, and 4 weeks after surgery. Bone repair and inflammation in each specimen was blindly graded by a pathologist. Reaction to the foreign body and the amount of the remaining chitosan were studied in chitosan-treated specimens at the three stages of the study. Statistical analysis was performed using Fisher's exact test and kappa test. A P value less than 0.05 was considered as significant. Results: Bone repair was significantly faster in the chitosan group, 1 week ( P = 0.01) and 4 weeks ( P = 0.038) after surgery, while the difference was not significant at the 2-week stage ( P = 0.197) between chitosan and control groups. Chitosan-induced inflammation was not significant in any stage of the study. Reaction to the foreign body was seen in one case at 2 weeks and one case at 4 weeks postoperation. Conclusion: Chitosan significantly accelerated the bone regeneration process in rat tibias. Regarding its biocompatibility and osteoinductivity, it can be studied as a biomaterial in human bone healing.